Islam dan Internet: Toleransi Beragama di Dunia Maya - Sandriansyah Sandriansyah (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2020)
Religious life is very dynamic, especially supported by increasingly advanced technological developments. Of course, the discussion of tolerance must follow the current technological developments because technological developments support it. With the existence of social media, people can gather through an Internet network called the virtual world, both from various countries and religions. This will create vulnerability to religious tolerance because the existence of social media conceivably allows people to show hatred towards other religions, to which according to them is against their religion. Relevant to the studied object, this research is included in the type of library research. Sources of data used in this literature are derived from the Internet, such as YouTube